The Role of the Anion in Salt (NaCl) Detection by Mouse Taste Buds - Roebber, Jennifer K. (J Neurosci, 2019)
How taste buds detect NaCl remains poorly understood. Among other problems, applying taste-relevant concentrations of NaCl (50–500 mm) onto isolated taste buds or cells exposes them to unphysiological (hypo/hypertonic) conditions. To overcome these limitations, we used the anterior tongue of male and female mice to implement a slice preparation in which fungiform taste buds are in a relatively intact tissue environment and stimuli are limited to the taste pore. Taste-evoked responses were monitored using confocal Ca(2+) imaging via GCaMP3 expressed in Type 2 and Type 3 taste bud cells. NaCl evoked intracellular mobilization of Ca(2+) in the apical tips of a subset of taste cells. The concentration dependence and rapid adaptation of NaCl-evoked cellular responses closely resembled behavioral and afferent nerve responses to NaCl. Importantly, taste cell responses were not inhibited by the diuretic, amiloride. Post hoc immunostaining revealed that >80% of NaCl-responsive taste bud cells were of Type 2. Many NaCl-responsive cells were also sensitive to stimuli that activate Type 2 cells but never to stimuli for Type 3 cells. Ion substitutions revealed that amiloride-insensitive NaCl responses depended on Cl(−) rather than Na(+). Moreover, choline chloride, an established salt taste enhancer, was equally effective a stimulus as sodium chloride. Although the apical transducer for Cl(−) remains unknown, blocking known chloride channels and cotransporters had little effect on NaCl responses. Together, our data suggest that chloride, an essential nutrient, is a key determinant of taste transduction for amiloride-insensitive salt taste. SIGNIFICANCE STATEMENT Sodium and chloride are essential nutrients and must be regularly consumed to replace excreted NaCl. Thus, understanding salt taste, which informs salt appetite, is important from a fundamental sensory perspective and forms the basis for interventions to replace/reduce excess Na(+) consumption. This study examines responses to NaCl in a semi-intact preparation of mouse taste buds. We identify taste cells that respond to NaCl in the presence of amiloride, which is significant because much of human salt taste also is amiloride-insensitive. Further, we demonstrate that Cl(−), not Na(+), generates these amiloride-insensitive salt taste responses. Intriguingly, choline chloride, a commercial salt taste enhancer, is also a highly effective stimulus for these cells.